2011
DOI: 10.1002/app.33513
|View full text |Cite
|
Sign up to set email alerts
|

Tensile fatigue, stress relaxation, and creep behaviors of worsted core spun yarns

Abstract: The objective of this research was to investigate the time-dependent behaviors of yarns, which have significant bearings upon the properties of stretch fabrics made from them. In this study, 100% wool, wool-lycra (W-L) (97 : 3), and polyester-wool-lycra (P-W-L) (52 : 45 : 3) blended yarns were considered. These yarns were subjected to the tensile fatigue failure, stress relaxation, and creep experiments. The findings showed that of these three yarns, P-W-L blend exhibited maximum fatigue lifetime, stress reten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…There is currently limited information about the mechanical properties of yarns processed in the United States, which influenced the inclusion of tensile strength testing in this study. At the yarn level, tensile strength studies compare wool and synthetic yarns but do not provide a comparison of diverse natural yarns such as wool, alpaca, and mohair (Bandyopadhyay, Ghosh, & Ali, 2011; Treigien_ e & Laureckien_ e, 2012). Tensile strength is critical since it conveys the ability of the yarn to endure stress with mechanically induced tension from knitting or weaving processes.…”
Section: Made In United States and Natural Fibersmentioning
confidence: 99%
“…There is currently limited information about the mechanical properties of yarns processed in the United States, which influenced the inclusion of tensile strength testing in this study. At the yarn level, tensile strength studies compare wool and synthetic yarns but do not provide a comparison of diverse natural yarns such as wool, alpaca, and mohair (Bandyopadhyay, Ghosh, & Ali, 2011; Treigien_ e & Laureckien_ e, 2012). Tensile strength is critical since it conveys the ability of the yarn to endure stress with mechanically induced tension from knitting or weaving processes.…”
Section: Made In United States and Natural Fibersmentioning
confidence: 99%
“…Due to the high differences in structure of fibres, the relaxation behaviour could be different and it is especially visible for woollen fibres, as the protein fibres have an even more complex physical and chemical structure. Therefore, it was found that the stress relaxation behaviour in long-lasting relaxation (more than 10,000 s) exhibits some difference from the behaviour in a short time relaxation [2,8,13,16,[23][24][25][26][27][28][29]32]. The stress relaxation in initial time of relaxation can …”
Section: Methodsmentioning
confidence: 99%
“…Van Miltenburg [18] investigated the relation between tensile modulus and stress relaxation and found that the modulus-elongation curve of different fibres (polyester, polyamide, viscose rayon and aramid) strongly correlates with the residual stress. The stress relaxation behaviour of natural fibers were studied by many researchers [22][23][24][25][26] too. Wool, silk and cotton exhibit similar behaviour in the early process of stress relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have reported that the modelling of yarn can be formulated by analytical mechanics and simulated using computer programs [18,19,20,21,22,23,24,25]. Therefore, this research aims to make a better model of the material properties of textile yarns, especially for the stress relaxation model, using an example of polyester-woolspandex yarn with an analytical mechanics approach [26][27][28][29][30][31][32][33][34]. In this model, the research limitation is that it does not involve the presence of stress and strain tensors studied from the point of view of the geometric structure of the yarn and polymer molecular dynamics.…”
Section: Introductionmentioning
confidence: 99%